Staphylococcus aureus bacteremia with iliac artery endarteritis in a patient receiving ustekinumab. Issue 1 (December 2016) - Joost, Insa; Steinfurt, Johannes; Meyer, Philipp; Kern, Winfried; Rieg, Siegbert
Abstract Background Ustekinumab (Stelara®), a human monoclonal antibody targeting the p40-subunit of interleukin (IL)-12 and IL-23, is indicated for moderate to severe plaque psoriasis and psoriatic arthritis. In large multicenter, prospective trials assessing efficacy and safety of ustekinumab increased rates of severe infections have not been observed so far. Case presentation Here, we report the case of a 64-year old woman presenting with chills, pain and swelling of her right foot with dark maculae at the sole, and elevated inflammatory markers. She had received a third dose of ustekinumab due to psoriatic arthritis three days before admission. Blood cultures revealed growth ofStaphylococcus aureus and imaging showed a thickening of the aortic wall ventral the bifurcation above the right internal iliac artery, resembling an acute bacterial endarteritis. Without the evidence of aneurysms and in absence of foreign bodies, the decision for conservative management was made. The patient received four weeks of antibiotic therapy with intravenous flucloxacillin, followed by an oral regime with levofloxacin and rifampicin for an additional four weeks. Inflammatory markers resolved promptly and the patient was discharged in good health. Conclusion To our knowledge, this is the first report of a severeS. aureus infection in a patient receiving ustekinumab. Albeit ustekinumab is generally regarded as a safe drug, severe bacterial infections should always be included in the differential diagnosis of elevated inflammatory markers in patients receiving biologicals as these might present with nonspecific symptoms and fever might be absent. Any effort to detect deep-seated or metastatic infections should be made to prevent complications and to secure appropriate treatment. Although other risk factors for an invasive staphylococcal infection like psoriasis, recent corticosteroid injection, or prior hospitalisations were present, and therefore a directive causative link between theS. aureus bacteraemia and ustekinumab can not be drawn, we considered the reporting of this case worthwhile to alert clinicians as we believe that ongoing pharmacovigilance to detect increased risks for rare but severe infections beyond phase II and phase III trials in patients treated with biologicals is essential.